Self-acceptance dan dukungan sosial online dengan kecenderungan body dissatisfaction pengguna instagram pada masa emerging adulthood - Laiyusa Ananda Fitrianti; Amanda Pasca Rini; Nindia Pratitis (INNER: Journal of Psychological Research, 2022)
Abstract The purpose of this study was to determine the relationship between self-acceptance and online social support with the tendency of body dissatisfaction among Instagram users in emerging adulthood. This research was conducted on 117 Instagram users with an age range of 18-29 years. Samples were taken using the purposive sampling technique. This study uses multiple regression analysis with the help of SPSS version 25.0 for windows. The results of the analysis showed that the relationship between self-acceptance and online social support was 0.356 with a significance of p=0.000 (p<0.01). The relationship between self-acceptance and the tendency of body dissatisfaction is -0.262 with a significance of p=0.094 (p>0.05). This shows that the level of self-acceptance in a person does not affect body dissatisfaction. As for the relationship between online social support and body dissatisfaction, the results show that there is a very significant relationship. This shows that Instagram users in emerging adulthood have a high tendency of body dissatisfaction and receive the same high online social support with a regression correlation value of 1.148 and a significance of 0.000 (p<0.01). Keywords: Body Dissatisfaction; Emerging Adulthood; Online Social Support; Self-Acceptance.